Factors Influencing Yaws Disease in Bambakaenu Village, Pinembani District, Donggala Regency - Rusno Harami, Anwari; Budiman, Budiman; Reza Alief Chairun Nur, Andi (Universitas Muhammadiyah Palu, 2020)
Yaws is a contagious disease caused by Treponema pertenue bacteria. Yaws is one of a group of diseases that spread without a host but occurs by direct contact. Yaws disease is strongly influenced by low socio-economic levels, occupancy density, clean water supply, and personal hygiene. This study aimed to determine the factors of yaws disease, including pure water supply, house conditions, and bathing habits. This type of research is analytical survey research with a cross-sectional approach. This research was conducted in Bambakaenu Village, Pinembani District, Donggala Regency in January 2020, with a sample of 86 respondents. The results showed no relationship between clean water supply and yaws, as proven by statistical tests with a p-value of 0.629> 0.05. Meanwhile, the results showed an association between house conditions and yaws, as confirmed by statistical tests with a p-value of 0.002 <0.05. The results showed no relationship between bathing habits and yaws, as proven by statistical tests with a p-value of 0.786> 0.05. It is expected for the community to maintain and always maintain personal and environmental hygiene by still trying to behave clean and healthy to reduce the transmission of yaws disease